Video-Assisted Thoracoscopic Surgery for Pulmonary Sequestrations: Series of 35 Consecutive Patients in a Single Center - Wang, Shaodong; Li, Yun; Wang, Jun (The Thoracic and Cardiovascular Surgeon, 2019)
Objective The aim of this report is to summarize the experience of completely video-assisted thoracoscopic surgery (VATS) for pulmonary sequestration in a single center and to evaluate the long-term outcome in a larger series of patients.Methods The data of 35 pulmonary sequestrations who received completely VATS consecutively in Peking University People's Hospital between January 2008 and November 2017 were retrospectively reviewed. Twenty-three females and twelve males with an average of 38 years old were included.Results A total of 28 (80%) patients had preoperative symptoms; leading symptoms were recurrent infections (22), fever (11), hemoptysis (11), chest pain (9), and shortness of breath (4). Twenty-nine (82.9%) patients were intralobar pulmonary sequestration (22 in the left lower lobe, 6 in the right lower lobe, and 1 in the left upper lobe) and six (17.1%) patients were extralobar pulmonary sequestration. All the patients underwent VATS excision successfully, 26 underwent lobectomy, 2 underwent wedge resection, 1 underwent occlusion of the aberrant artery, and 6 underwent mass resection in all of those with extralobar pulmonary sequestration. The median surgery time and estimated blood loss was 150 (75–300) minutes and 50 (10–600) mL, respectively. There was no mortality. Only one patient suffered postoperative complication (recurrent laryngeal nerve injury). During the median follow-up period of 57 months, none of the patients presented recurrence.Conclusions Completely VATS was a safe and effective mini-invasive procedure for pulmonary sequestration in an experienced team. Its long-term outcome was remarkable.
Keywords: pulmonary sequestration; VATS; treatment